Holistic well-being of Japanese retirees in Malaysia - Alby, Jeffrey Lawrence D’Silva; Abu Samah, Asnarulkhadi (Center of Sociological Research, 2018)
The current era of extensive use of information and communication technology and globalization brought the mankind to pay attention to the wellbeing of people as it is paramount for sustainable development of communities. Accordingly, numerous discussions were put forward to conceptualize well-being as such. Judging from the literature, holistic well-being is deemed as a better form of measuring well-being as it incorporates both objective and subjective dimensions. The aim of this study is to examine the holistic well-being of Japanese retirees residing in Malaysia. Data were collected from 278 retirees via a pick-and-drop method as well as face-to-face interviews. The findings show that the holistic well-being of Japanese retirees in Malaysia is 56.3%. Besides, the study has identified that these retirees scored as the highest the dimensions of communication technologies and lifestyle. On the other hand, the lowest scores got the dimensions of political and physical facilities. It is proposed that to further enhance the international retirement migration, particularly in the Malaysian context, political stability and good physical facilities are the pertinent factors that need to be emphasized.